Potensi Makanan Tradisional Kabupaten Jombang sebagai Sumber Belajar Struktur Perkembangan Tumbuhan - Ami, Mucharommah Sartika; Yuliana, Anggi Indah (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2020)
Traditional cuisines have pedagogy values that can be used as learning source. Jombang traditional cuisines haven’t used yet as a biology learning source, especially for plant structure and development material. This research explored Jombang’s traditional cuisines that can be used as plant structure and development learning sources. This is qualitative research with an ethnographic approach. Data collected by interview and observation. Data analyzed by domain analysis and taxonomical analysis. There are three Jombang’s traditional cuisines that were famous as culinary icons,namely Pecel Rengkek, Sego Ampok, and Lodeh Kikil.The three types of traditional food have raw materials, which are mostly in the form of plants, with the types and parts of the plant’s body that are quite relevant and potential as a source of learning to study the concepts of the plant structure and development. Monocot and dicot plants are included in the raw materials for the three types of traditional foods. The parts of the plant body that are used in the manufacture of the three types of traditional food include all plant organs, namely roots, stems, leves, flowers, fruits, and seeds.